Design Analysis of Solar-Powered Unmanned Aerial Vehicle - Sri,Karthik Reddy Buchireddy (2016)
ABSTRACT One of the main problems in micro unmanned aerial vehicles is endurance or flight time since the general domain aircraft uses conventional fuel, which is a pollutant, has a limited life and is costly. Then, there is a huge demand for using an unlimited non-exhaustible source of energy. Solar energy is one of the unlimited available renewable energy which can be used to increase the endurance of unmanned aerial vehicle without adding significant mass or increasing the size of the fuel system. This paper aims to encourage research on renewable energy sources for aviation considering the basic challenges for a solar-powered aircraft: geographical area of operation, energy collection and storage, payload and design parameters. Hence, a plane is designed for 2 kg, including payload, and is analyzed in various aspects. Besides, the design is optimized starting from airfoil to complete structure for better performance.